New challenges to the separation of powers dividing power - Baraggia, Antonia; Fasone, Cristina; Vanoni, Luca P. (Edward Elgar Publishing, 2020)
This insightful book guides readers through the transformation of, and theoretical challenges posed by, the separation of powers in national contexts. Building on the notion that the traditional tripartite structure of the separation of powers has undergone a significant process of fragmentation and expansion, this book identifies and illustrates the most pressing and intriguing aspects of the separation of powers in contemporary constitutional systems. Chapters explore the social foundations of the doctrine of the separation of powers, its relationship to direct democracy, the role of constitutional courts and the rise of the administrative state. Expert contributors analyse power structures and the separation of powers across new constitutions in central Europe, examining the transformations of political parties and testing the limits of the doctrine alongside a reimagining of the judicial review process. This timely book concludes with a historical perspective on the doctrine and a case study considering a possible new separation of powers in North Africa and the Middle East. This unique book will be of interest to students and academics of comparative constitutional law, as well as constitutional and political theorists, lawyers and judges"--